Protocol for culturing and imaging of ectodermal cells from Xenopus - Nydia Tejeda-Muñoz; Julia Monka; Edward M. De Robertis (STAR Protocols, 2022)
Summary: The Xenopus embryo provides an advantageous model system where genes can be readily transplanted as DNA or mRNA or depleted with antisense techniques. Here, we present a protocol to culture and image the cell biological properties of explanted Xenopus cap cells in tissue culture. We illustrate how this protocol can be applied to visualize lysosomes, macropinocytosis, focal adhesions, Wnt signaling, and cell migration.For complete details on the use and execution of this protocol, please refer to Tejeda-Muñoz et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.